2011
DOI: 10.1007/s11684-011-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of superparamagnetic iron oxide nanoparticles in targeted therapy and imaging of cancer

Abstract: Superparamagnetic iron oxide (SPIO) nanoparticles have become a popular strategy of cancer treatment and molecular imaging because of their versatile properties and biocompatibility. A variety of studies have shown the exciting potential of functionalized SPIO nanoparticles, such as surface-coated, targeted ligandconjugated, and/or drug-loaded SPIO nanoparticles, as powerful tools for targeted imaging and therapy. Moreover, the applications of SPIO nanoparticles that integrate diagnosis and therapy in SPIO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…[1][2][3][4] However, the difficulty of evaluating and determining the precise contribution of each mechanism involved in cell-based treatments is one of the obstacles to their approval for clinical use. 5,6 Methods to determine the biodistribution and fate of injected cells are required to understand and refine stem cell therapies in patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, the difficulty of evaluating and determining the precise contribution of each mechanism involved in cell-based treatments is one of the obstacles to their approval for clinical use. 5,6 Methods to determine the biodistribution and fate of injected cells are required to understand and refine stem cell therapies in patients.…”
Section: Introductionmentioning
confidence: 99%
“…120 In another study, the authors were able to follow SPION-labeled bone marrow progenitor cells by MRI in heart tissue for weeks after intracoronary injection, but a very large number (13×10 6 ) of cells were used in this study. 121 Also using a very large number (100×10 6 ) of SPION-labeled mesenchymal stem cells delivered by intrapericardial administration in porcine models, the authors identified a significant number of cells retained in the cardiac tissue a few days after injection. 122 In small rodents, it was possible to observe SPION-labeled mesenchymal stem cells (Endorem) after direct injection into the myocardial infarction scar.…”
mentioning
confidence: 99%
“…The nanoscale structure and features of superparamagnetism offer a variety of possibilities for treatment and diagnostic medical applications. 1 SPIONs are used as tracer material in magnetic particle imaging (MPI). MPI was introduced in 2005 as a novel tomographic imaging modality.…”
Section: Introductionmentioning
confidence: 99%
“…NPs possess unique properties that enable them to be used as imaging probes, which may be traced via magnetic resonance imaging (MRI) and therapeutic agents at the same time (14); however, they can be further loaded to deliver specific drugs (15)(16) or target specific molecules (17,18). Superparamagnetic iron oxide (SPIO), known to be a highly efficient T 2 contrast agent for MRI, is an ideal small molecular probe for medical use (19). Although SPIO exploit an enhanced permeability and retention effect (EPR) for tumor uptake, EPR is still inefficient with relatively low concentrations of NPs reaching tumors (20).…”
Section: Introductionmentioning
confidence: 99%